THE PECULIARITIES OF ECOLOGICAL EVALUATING NATURAL-ANTHROPOGENIC IMPACT ON HYDROSPHEREWITHIN URBAN TECHNO-ECOSYSTEMS - Podrezenko, I. N.; Ostapenko, N. S.; Kriuchkova, S. V.; Kirichenko, V. A.; Bondarenko, L. V. (Scientific Progress & Innovations, 2019)
Hydrosphere ecosystems are of great importance for the functioning of urban techno-ecosystems. Their ecological condition is mostly influenced by production processes of enterprises, especially mining, which use huge amounts of resources (energy, materials, and water), and return a lot of wastes and polluted wastewater to the environment. The analysis of long-term observations shows that the most common pollutants of the Dnieper basin’s rivers are nitrites, ammonium nitrogen, biogenic and organic substances, heavy metals, petroleum products, and phenols. Their concentration points to the violation of water quality standards, which have been approved for industrial-economic complexes, reservoirs for fish farming, as well as cultural and community purposes within urban techno-ecosystems. One of the main tasks of ecologically balanced environmental management must be determining the multicomponent impact of toxic emissions and wastes on the environment, especially on the hydrosphere, aimed not only at overcoming the negative consequences, but also preventing the anthropogenic impact. Methodological approaches to assessing naturalanthropogenic influence on the hydrosphere within urban techno-ecosystems are presented. In this research, it is suggested to evaluate natural-anthropogenic impact on hydrosphere by determining the pair correlation at the microelement level. The urgency of this problem is also stipulated by the fact that in recent years there has been a tendency to secondary pollution of natural waters due to the desorption of pollutants of various nature and chemical structure in the corresponding sediments. For the first time, the correlation relationships between the anthropogenic, biogenic, and hydrological characteristics of reservoirs within the urban techno-ecosystems have been investigated; pair-correlation coefficients have been determined; the systematization has been carried out and the main regularities concerning the distribution of microelements in seven groups, taking into account their quantitative content in plankton, has been conducted. As a result of the analysis of pair correlation coefficients between the microelements contained in plankton, the danger classification of these microelements has been made concerning their transfer in the “Plankton/Fish/Human” food chain.